MENTAL CHARACTERISTICS OF AGGRESSIVE ACTION IN PRIMARY SCHOOL AGE - Konratbaeva Ayjamal Bazarbaevna (Galaxy International Interdisciplinary Research Journal, 2022)
The article is devoted to the actual topic of aggression in children of primary school age. Aggressiveness in children has a specific character, and this specificity manifests itself especially sharply in adolescence and primary school age. The analysis of the classification of the aggressive behavior of schoolchildren. The development of aggressiveness in primary schoolchildren is influenced by the natural characteristics of temperament, excitability and the strength of the emotions of the nervous system, which contributes to the formation of such traits as hot temper, irritability, inability to restrain oneself.